Dynamic contact area ratio in shoulder instability: an innovative diagnostic technique measuring interplay of bony lesions - Weel, Hanneke (Knee Surg Sports Traumatol Arthrosc, 2019)
PURPOSE: The hypothesis of this study is that Dynamic Contact Area Ratio of the humerus and glenoid, measured with CT scans, is significantly reduced in patients with anterior shoulder instability compared to the Dynamic Contact Area Ratio in a control group of people without shoulder instability. METHODS: Preoperative CT scans of patients who underwent surgery for anterior shoulder instability were collected. Additionally, the radiologic database was searched for control subjects. Using a validated software tool (Articulis) the CT scans were converted into 3-dimensional models and the amount the joint contact surface during simulated motion was calculated. RESULTS: CT scans of 18 patients and 21 controls were available. The mean Dynamic Contact Area Ratio of patients was 25.2 ± 6.7 compared to 30.1 ± 5.1 in healthy subjects (p = 0.014). CONCLUSION: Dynamic Contact Area Ratio was significantly lower in patients with anterior shoulder instability compared to controls, confirming the hypothesis of the study. The findings of this study indicate that calculating the Dynamic Contact Area Ratio based on CT scan images may help surgeons in diagnosing anterior shoulder instability. LEVEL OF EVIDENCE: III. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00167-019-05816-5) contains supplementary material, which is available to authorized users.